2013
DOI: 10.1002/pca.2462
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Distribution in Liquid Preparations of Vaccinium myrtillus L. and Vaccinium vitis idaea L.

Abstract: The analytical method allowed to define fingerprints of bilberry and lingonberry liquid preparations. Moreover, without applying accelerated ageing protocols, the stability over time of 11 samples was evaluated up to 6 months, demonstrating negligible variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
86
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 16 publications
7
86
0
7
Order By: Relevance
“…Antibacterial, anti-inflammatory, hypoglycaemic, and hypolipidemic activities are also associated with bilberry leaves. [12] Many phenolic compounds have been identified in bilberries and differences in their phenolic profiles have been observed and linked to numerous factors. Anthocyanins represent the most important group in bilberries, contributing to their attractive purple-blue colour hues but also defining quality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial, anti-inflammatory, hypoglycaemic, and hypolipidemic activities are also associated with bilberry leaves. [12] Many phenolic compounds have been identified in bilberries and differences in their phenolic profiles have been observed and linked to numerous factors. Anthocyanins represent the most important group in bilberries, contributing to their attractive purple-blue colour hues but also defining quality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in case of consumption, the content of toxic arbutin should be taken into consideration, as it is a hydroquinone derivate (YANG & JIANG, 2010;IERI et al, 2013;NILE & PARK, 2014). According to our best knowledge, this compound is detected in lingonberry and blueberry (YANG & JIANG, 2010;IERI et al, 2013). Recent studies also showed, that the urinary use of the polyphenol-rich herbs may have unexpected side effects, because they modulated and sometimes enhanced the bacterial antibiotic susceptibility (SAMOILOVA et al, 2014).…”
mentioning
confidence: 99%
“…All in all, the berries have signifi cant antioxidant contents, but the antioxidant properties can change in wide ranges in the species themselves as well as between species (IERI et al, 2013). Our aim was to determine the antioxidant properties, especially the inhibition of lipid peroxidation of blueberry, bilberry, and lingonberry available in the northern regions of Europe, to evaluate their protective effect in some gastrointestinal cases with disrupted redox homeostasis, which is a serious problem in this region.…”
mentioning
confidence: 99%
See 2 more Smart Citations